Labour productivity in the Nordic EU countries - a comparative overview and explanatory factors – 1998-2004 - Anatoli Annenkov; Christophe Madaschi (European Central Bank (ECB), 2005)
This paper analyses the differences in hourly labour productivity growth rates and levels between the Nordic EU countries (Denmark, Finland and Sweden) and four larger euro area countries (Germany, France, Italy and Spain). Additional information for the euro area as a whole, the UK and the US is also provided. Given that the economic and social models developed in the Nordic EU countries are in many ways closer to those of the larger euro area countries than that of the US, the experience of these countries is particularly interesting. Since the mid-1990s, the Nordic EU countries, particularly Sweden and Finland, have experienced stronger labour productivity growth than the larger euro countries. Like in the US, innovation and technological changes have played a major role in explaining the higher labour productivity growth in the Nordic EU countries compared with the larger euro area economies. Information and Communication Technology (ICT) diffusion is a key element to explain these differences. A number of institutional indicators, relating to market regulation, human capital, R&D investments and venture capital, show that the Nordic EU economies are better positioned than some of the larger euro area countries to exploit the opportunities provided by ICT in terms of productivity growth. However, remaining labour market rigidities may not allow the Nordic EU countries to fully enjoy the benefits of ICT diffusion in terms of increased employment.
Keywords: 330; Arbeitsproduktivität; Nordeuropa